PROBLEMATIKA PENDIDIKAN AGAMA DALAM KELUARGA TERHADAP PERILAKU ANAK DI ERA DIGITAL (STUDI KORELASI DI NEGERI KAILOLO PULAU HARUKU): - - Sahartira, Nur; Adam Latuconsina; Rustina N. (Jurnal Studi Islam, 2025)
Abstract: Religious education in the digital era is very important to protect the misuse of applications and features that are increasingly developing on social media. The problem of this research is how is children’s religious education in the family Kailolo Country, Haruku Island District? How big Is the influence between children’s religious education on children’s behavior in Negeri Kailolo, Haruku Island District? Thus, this research aims to examine the problems of children’s religious education in families in Kailolo Island, Haruku Island District, and analyze the influence of religious education on children’s behavior in Kailolo Country, Haruku Island District, Central Maluku Regency. The type of research used is correlation with a quantitative descriptive approach, to describe the influence of children’s religious education on families in Kailolo State with a research sample of 30 children. Data collection and processing techniques are carried out through questionnaires and documentation as well as data analysis techniques using correlation tests. The results of this research show that the implementation of children’s religious education in families in Kailolo State is quite effective and is maximally implemented in the religious education aspect with a percentage of 52.22%, in the religious education aspect it is less than optimal with a percentage of 41.67%, and in the moral education aspect it is less than optimal with a percentage of 42.38%. And the correlation between children’s religious education and children’s behavior is 0.777, where at 5% significance it is 0.361 and at 1% significance it is 0.463. The contribution of children’s religious education to children’s behavior is 60.373%. So it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a significant influence between children’s religious education on children’s behavior Keywords: Children’s education, Family Education, Digital Era. Kailolo Country